Nucleocapsid Protein of Newcastle Disease Virus as an Antigenic Carrier - Rabu, Amir (2002)
Newcastle disease virus (NDV) is an economically important avian virus that causes loss to the poultry industry. It has a wide host range infecting 27 of the 50 orders of birds. Generally, the virus consists of six structural proteins: nucleocapsid (NP), phosphoprotein (P), matrix (M), fusion (F), haemagglutinin-neuramidase (HN) and large (L). The NP protein resembles the classical herringbone morphology when observed under electron microscope. However, the morphology changed into individual ring-like particles when the myc epitope and six histidine residues were fused to the C-terminal end of the protein. Further investigation showed that the C-terminus of this protein derivative is exposed on the surface of the ring-like particles. In this project, several chimeric proteins have been constructed in which the antigenic regions of the HN or F protein of NDV strain AF2240, myc epitope and six histidine residues were linked to the C-tenninus of the NP protein. The chimeric proteins were expressed efficiently in Escherichia coli as detected by Western blot analysis. Electron microscopic analysis on these proteins revealed that they assembled into ring-like particles. These chimeric NP proteins exhibited antigenicity of the myc epitope suggesting that the foreign sequences were exposed on the surface of the particles. Chickens vaccinated with the chimeric particles exhibited an immune response against NDY. However, no protection was observed when the vaccinated chickens were challenged by the virus.